Link and Match dalam Pendidikan Islam (Keterkaitan dan Kesepadanan Pendidikan Islam dengan Dunia Kerja) - Musayyidi Musayyidi; Ach Syaiful; Hafid Hafid (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2026)
National education in Indonesia faces internal and external challenges that require relevance to the needs of the world of work and technological development. This research aims to analyze the concept of Link and Match in Islamic education as a strategy to produce graduates who are skilled, work-ready, and faithful. The method used is literature review by analyzing various theoretical sources related to Link and Match, Islamic education, and its relevance to changes in times. The results show that the concept of Link and Match in Islamic education is a relevant and flexible strategy to overcome the gap between educational output and modern job market needs. This concept emphasizes the linkage and alignment between education and development in accordance with Islamic teachings, which have been taught since ancient times in the Qur'an and Hadith of the Prophet. The application of Link and Match can be implemented through school-workplace partnerships, curriculum innovation, development of skills-based extracurricular activities, and enhanced work ethic among all stakeholders. The implications of this research show that serious implementation of the Link and Match concept can shape young generations capable of competing in the global era while maintaining Islamic values.